Experimental study on creep characteristics of electrolyte-bearing salt rock under long-term triaxial cyclic loading - Huang, Si; Lu, Jun; Wang, Jian; Fu, Xinghui; Fu, Yaping; Li, Yinping; Shi, Xilin; Dong, Zhikai; Zhao, Kai; Li, Peng; Xu, Mingnan; Chen, Xiangsheng (Frontiers in Earth Science, 2024)
During the operation of the Salt Cavern Flow Battery (SCFB) system, the rock surrounding a salt cavern is subjected to erosion by the electrolyte. To study the creep characteristics of electrolyte-bearing salt rock under long-term triaxial cyclic loading in SCFB, a triaxial creep experiment with a cycle period of 1 day was conducted. The results indicated that, when not subjected to failure, the axial stress-strain curve of electrolyte-bearing sample undergoes only two phases of “sparse-dense”, entering dense phase approximately 4 cycles earlier than that of sample without electrolyte. Under the same stress conditions, the strain generated in electrolyte-bearing salt rock surpasses that of sample without electrolyte, demonstrating an initial rapid increase followed by a gradual stabilization trend. The stress-strain curve of electrolyte-bearing sample in a single cycle can be divided into six stages. The number of cycles has almost no effect on the axial strain in stages I, IV, V and VI, and the axial strain in stages IV and VI is basically 0. Additionally, the elastic deformation generated in stage I is basically recovered in stage V. The strain in stage II gradually decreases and disappears in the 4th cycle, which is 13 cycles earlier than that of the sample without electrolyte. The creep rate of electrolyte-bearing sample shows a trend of “gradual decrease—basically stabilization” as the number of cycles increases, and the creep experiment contains only the decay creep stage and steady creep stage. Irreversible deformation of electrolyte-bearing sample exhibits a gradual decrease followed by stabilization with increasing number of cycles. The research findings hold significant implications for the stability analysis of SCFB systems.